Investigating the Eight Graders' Interest in Learning English at SMP YPK Hedam Abepura - Encelina Yaroseray; Servo Kocu; Maximus Nemo (FKIP Universitas Cenderawasih, 2023)
This research aims to determine interest in learning and the factors that influence students' interest in learning in eighth grade students at YPK Hedam Abepura Middle School, Jayapura. The design of this research is descriptive-qualitative, using questionnaire instruments, observation, and documentation. The subjects in this research were 25 students in VIII A and 1 English teacher. The results of this research show that the interest in learning English of eighth grade students at YPK Hedam Middle School is very low. However, it is caused by various factors. The factors that influence students' interest in learning are: a) internal factors; and b) external factors. From the results of this research, students showed In the first aspect of 25 respondents, there were 2,74 (55%) who did not have a feeling of pleasure when studying English, while the second aspect saw 3,68 (74%) actively involved in learning English in class, the third aspect 3,23 (65%) who had an interest in learning English, and the last aspect 3,14 (63%) who seemed to focus on paying attention during English learning hours. Students feel unhappy when learning English, and the rest of them just follow English lessons without interest. From the results obtained, each aspect has clearly shown how students are doing in class when learning English, and students who do not have an interest in learning are also less (64,24%) maximum criteria score indicators of interest. Keywords: Investigate, Student interest, learning English